"I'm empowered to look after myself" — Mindfulness as a way to manage chronic pain: An interpretative phenomenological analysis of participant experiences in Scotland. (July 2021) - Marikar Bawa, Fathima L.; Sutton, Jane W.; Mercer, Stewart W.; Bond, Christine M.
Abstract: Background and Primary Aim: Chronic pain is a common problem that can impact on psychological and social wellbeing and activity levels. Despite pharmacological treatments, there is often a lack of improvement in physical and emotional functioning and health-related quality of life. Mindfulness meditation has become an increasingly popular self-management technique. The aim of the study was to explore the experiences of patients with chronic pain who took part in a mindfulness programme. Methods: A mixed-methods feasibility study was carried out. Participants were aged 18 years or over with non-malignant chronic pain recruited from general medical practices in Fort William, Scotland. In 2013 participants undertook an eight-week mindfulness programme based on Mindfulness-Based Stress Reduction (MBSR) and were interviewed immediately post-programme and at eight-months' post-programme. Analysis of qualitative data involved Interpretative Phenomenological Analysis (IPA). Findings: Thirty-four patients consented to take part in the study; twenty-four took part in the programme (14 attended four or more sessions, 10 attended one to three). Twenty-three were interviewed. Participant experiences of the programme were themed under: factors affecting experience (influence of earlier life events; the process of taking part in, and of relating to, the programme); and effects of the programme (impact on emotions, mental health, adverse events and a process of change). The process of change, resulting after better understanding the relationship between mindfulness and pain, involved learning to 'listen to the body', gaining a sense of community, learning to accept pain, and approaching life with more self-care, awareness, appreciation and empowerment. Conclusion: Participants reported a variety of experiences. For some, these included undergoing a process of change which may have supported them in living with their painful condition. This contributes to our understanding of how mindfulness could benefit people with chronic pain. Highlights: Earlier difficulties influenced participant experience of the mindfulness programme. Unfulfilled expectations about controlling pain led to dropout. Understanding the relationship between mindfulness and pain was key to engagement. Programme experience involved transitioning to pain acceptance and empowerment.